PENGARUH BENTUK DAN DOSIS PUPUK ORGANIK TERHADAP SIFAT KIMIA TANAH, KANDUNGAN HARA MAKRO DAUN DAN PERTUMBUHAN VEGETATIF BIBIT JERUK SIAM (Citrus nobilis lour) - Allysa Puspa Saraswati; S Sutopo; Syahrul Kurniawan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Orange is a national superior commodity that has an important role in increasing foreign exchange for the country. However, the development of citrus cultivation in Indonesia is still relatively low, probably due to soil fertility degradation. Therefore, this study aimed to analyze the effect of differences in the application of organic fertilizer (form and dose) and their interaction on soil chemical properties, nutrient concentration in the leaf (i.e. N, P, K), and growth in Siamese citrus seedlings. The treatments included the application of a combination of forms and doses of organic fertilizer, namely SD1 (powder dose 2 t ha-1), SD2 (powder dose 4 t ha-1), SD3 (powder dose 6 t ha-1), SD4 (powder dose 8 t ha-1), SD5 (powder dose 10 t/ha), GD1 (granule dose 2 t ha-1), GD2 (granule dose 4 t ha-1), GD3 (granule dose 6 t/ha), GD4 (granule dose 8 t ha-1) and GD5 (granule dose 10 t ha-1). The results showed that there was a significant difference in the interaction between form and dose of organic fertilizer only in the number of primary branches at 4 WAP (weeks after application) with the highest values was found in powder organic fertilizer at a dose of 8 t ha-1 and granules organic fertilizer at a dose 10 t ha-1. In addition, the application of powder organic fertilizer application had a higher plant height at 10-12 WAP as compared to the application of granule organic fertilizer.